Customer Perception of Service Quality - Sailaja, M. (IJRDO - Journal of Business Management, 2021)
Today’s digital world has completely changed the way people are using the services specially the digital or online service. The changing lifestyles , better education, increased income levels, with more women taking up jobs, information availability has not only changed their expectations but also the way perceive the quality of the service provided. In the banking sector too we have witnessed tremendous changes from the time digital technology was introduced creating a lot of competition among public and private sector banks. Service quality is a major determinant of customer satisfaction leading to customer loyalty In their endeavour to provide better service banks have to focus more on factors influencing service quality . Most of studies related to service quality have thrown light on the influence of demographic factors on service quality dimensions. The present study attempts to check whether there is any association between gender and service quality dimensions. The findings suggest that there is association between gender and reliability and responsiveness.